Structural design challenges and implications for high temperature concentrating solar power receivers. (February 2023) - Barua, Bipul; Messner, Mark C.
Graphical abstract: Highlights: Design rules for high temperature metallic receiver are proposed. Creep damage accumulation due to high thermal stresses controls the design. Circumferential thermal gradient is worse than axial net thermal expansion. Creep-fatigue damage accumulation increases with tube thickness. Time-fraction creep damage model may need reconsideration. Abstract: High operating temperatures along with diurnal cycling and high operating stresses bring many material and engineering challenges for concentrated solar power (CSP) receivers. Current design rules in ASME Boiler and Pressure Vessel (B&PV) Code for high temperature structural components were not intended for CSP components. The paper reviews the design rules in several sections of ASME B&PV Code in terms of their applicability in designing high temperature CSP receivers. With some restrictions and modifications, the conditions assumed in the design rules in Section III, Division 5 of ASME B&PV Code are found to closely resemble the loading conditions of CSP receiver, including accounting for the interaction between creep and fatigue damage. The paper applies the proposed design rules to an external tubular receiver design and discusses several lessons learned from the design study. The creep damage accumulation due to high thermal stresses resulting from circumferentially non-uniform flux distribution is found to control the design of CSP receivers. Several mitigation actions to improve the design life of receivers are also discussed.